A Coupled Elastoplastic Damage Model for Clayey Rock and Its Numerical Implementation and Validation. (20th March 2020) - Jia, Shanpo; Zhao, Zhenyun; Wu, Guojun; Wu, Bisheng; Wen, Caoxuan
Abstract : This paper presents a new constitutive model for describing the strain-hardening and strain-softening behaviors of clayey rock. As the conventional Mohr-Coulomb (CMC) criterion has its limitation in the tensile shear region, a modified Mohr-Coulomb (MMC) criterion is proposed for clayey rock by considering the maximal tensile stress criterion. Based on the results of triaxial tests, a coupled elastoplastic damage (EPD) model, in which the elastic and plastic damage laws are introduced to describe the nonlinear hardening and softening behaviors, respectively, is developed so as to fully describe the mechanical behavior of clayey rock. Starting from the implicit Euler integration algorithm, the stress-strain constitutive relationships and their numerical formulations are deduced for finite element implementation in the commercial package ABAQUS where a user-defined material subroutine (UMAT) is provided for clayey rock. Finally, the proposed model is used to simulate the triaxial tests and the results validate the proposed model and numerical implementation.